Deliberate Activities Of The board and its Significance - REDDY, MANCHIREDDY CHANDRA SEKHAR; RAO KODALI, DHANUNJAYA; SRINIVAS, Dr. KUMMARI; RAMESH, MANCHALA (The journal of contemporary issues in business and government, 2019)
New departments have been added to our publications and conferences, and new approaches have been incorporated in our research since the inception of M&SOM. Will they benefit the field in any significant way? Some regard them as a hindrance, resulting in a disjointed society that is unable to communicate effectively because its members do not share a common language. Others rejoice in the increased diversity we've achieved and the new frontiers it has opened up for scientific study. We contend that neither side is completely incorrect, nor completely accurate. We, too, maintain that we must contribute to an ever-expanding range of areas by employing all available methods of investigation.. The challenge of fragmentation is one that we share with the people who raised it earlier. To break out of its rut and have greater influence, the discipline has to raise meaningful questions and deliver fascinating answers. I avoid the trap of specificity (great solutions to narrowly defined topics), (ii) connect and actively interact with various audiences, and (iii) be brave to pioneer new fields of investigation. When it comes to many of today's most pressing problems, operations management is a critical component.